Sailing close to the wind? The effects of third birth policies in post-communist Hungary. - Zsolt Sped́er; Liv́ia Murinko\'; Liv́ia Sz. Olah́ (Hungarian Demographic Research Institute, 2017)
Post-communist governments in Hungary made serious efforts to stop the massive fertility decline that started with the fall of the communist reproductive system, or at least to reduce it. Two of several interventions by the Hungarian government - the lengthening of child-raising allowance ('full time motherhood') and of a new tax-relief system -, were aimed specifically at supporting those having three and more children. However, the relevant statistics have not shown a growing ratio of third or further children. Here the authors employ an event-history method and use the data of the Hungarian Generation and Gender Survey to examine whether the government interventions had an effect of encouraging partners with two children to have a third birth, and whether specific social groups displayed different behaviour in this respect. The policy interventions have been measured by period indicators. After controlling for standard factors affecting third birth, the authors concluded that indeed, the government interventions have a significant, and differentiated effect on third- birth risks. While the massive lengthening of the child-raising allowance increased the third-birth risk of those with low educational attainment, the introduction of a generous tax relief seems to have done likewise for those with a tertiary education.
Keywords: J13; 300; population policy; low fertility; third births